1986
DOI: 10.1139/f86-195
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Relationships in Freshwater Pelagic Ecosystems

Abstract: Relative impacts of bottom-up (producer controlled) and top-down (consumer controlled) forces on the biomass and size structure of five major components of freshwater pelagic systems (piscivores, planktivores, zooplankton, phytoplankton, and total phosphorus availability) were estimated. Predictions that emerge are (1) maximum biomass at each trophic level is controlled from below (bottom-up) by nutrient availability, (2) this bottom-up regulation is strongest at the bottom of the food web (i.e. phosphorus → p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
519
6
14

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 883 publications
(577 citation statements)
references
References 0 publications
37
519
6
14
Order By: Relevance
“…Furthermore, it has often been reported that fish such as tilapia, by recycling nutrients through excretion, eventually promote the production of phytoplankton in ponds and lakes (McQueen et al, 1986;Drenner et al, 1987;Lazzaro, 1987;Northcote, 1988;Elser et al, 1990). Without algal biomass control, an excessive algal bloom may occur, followed by a collapse of the algal population, an increase in ammonia concentration and an oxygen depletion (Rimon and Shilo, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has often been reported that fish such as tilapia, by recycling nutrients through excretion, eventually promote the production of phytoplankton in ponds and lakes (McQueen et al, 1986;Drenner et al, 1987;Lazzaro, 1987;Northcote, 1988;Elser et al, 1990). Without algal biomass control, an excessive algal bloom may occur, followed by a collapse of the algal population, an increase in ammonia concentration and an oxygen depletion (Rimon and Shilo, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…2). McQUEEN et al (1986) ont proposé que les effets des herbivores sont maximums dans les milieux oligotrophes et s'atténuent avec l'augmentation de l'eutrophie, notamment du fait du développement d'algues peu consommables et de cyanobactéries filamenteuses, tandis qu'ELSER et GOLDMAN (1991) appuient l'hypothèse d'effets maximums des cascades trophiques en milieux mésotrophes où la prédation des poissons planctonophages et l'abondance des herbivores sont suf-…”
Section: Interactions Entre Les Ressources Et La Structure Des Réseauunclassified
“…Effets descendants des prédateurs atténués dans les lacs eutrophes du fait de la présence d'algues peu consommables (cyanobactéries filamenteuses ou coloniales) (a) effets en cascade des poissons maximal dans les lacs mésotrophes (b) faibles probabilités de rencontre entre prédateurs et proies dans les lacs oligotrophes (c) algues peu consommables empêchant le contrôle du phytoplancton par le zooplancton dans les lacs eutrophes (a) apports en nutriments déstabilisant les interactions trophiques (b) en présence de grand zooplancton herbivore, apports plus intenses nécessaires à la déstabilisation (a) phytoplancton contrôlé par le zooplancton si charge externe en PT < 0,6 g/m 2 /an (en liaison avec la taille maximale des colonies d'algues consommables) (b) efficacité des biomanipulations dépendante de la dynamique de P mobilisé dans macrophytes et poissons (a) proportion de poissons planctonophages augmentant avec l'eutrophie des lacs (de 50 % des poissons de plus de 10 cm à 22 p.gPT/L à 80 % à plus de 100 ug PT/L) (b) à long terme, élimination des planctonophages -» réduc-tion des algues uniquement si P = 0,5-2,0 g/m 2 /an (ou P = 80-150 ugP/L en été) (c) restauration plus efficace dans les lacs plats (à algues vertes) que dans les lacs profonds (avec blooms de cyanobactyéries), du fait du rôle épurateur des macrophytes submergés et des algues microbenthiques McQUEEN et al, 1986ELSER et GOLDMAN,1991CARPENTER étal., 1992BENND0RF, 1990 JÈPPESENefa/., 1990 fisamment importantes pour exercer un contrôle du phytoplancton. Les modèles proies-dépendants (PERSSON étal.…”
Section: Tableauunclassified
“…So the observed cascading effects give only a birds eye view of interplay and feed backs actually operating in an ecosystem. According to McQueen's (1986) model the interactions in the food chain gradually, weaken downwards in the chain but this can only be seen when just a small part of the food web is considered. For example in shallow, eutrophic Dutch lakes, which have virtually no macro-vegetation, it is, as regards fish, difficult to determine a planktivorous and a piscivorous fish.…”
Section: Biomanipulation and Ecosystem Researchmentioning
confidence: 99%